Perceptions and experiences of drug-resistant tuberculosis, HIV, and AIDS patients who experience loss to follow-up based on life values and stigma: a phenomenological study - Ikhwan Amirudin; Agung Waluyo; Astuti Yuni Nursasi; Dian Ayubi (Physical Therapy Journal of Indonesia, 2025)
Background: Human immunodeficiency virus (HIV), acquired immunodeficiency syndrome (AIDS), and tuberculosis are closely related and remain serious problems despite the implementation of various treatment strategies, but cases continue to increase. This research aimed to explore the perceptions and experiences of drug-resistant tuberculosis people with HIV/AIDS who experience loss of follow-up based on life values and stigma. Methods: This qualitative study employed a phenomenological approach and (COREQ) guidelines. Researchers purposively sampled participants with HIV/AIDS and tuberculosis in Lampung Province, Indonesia. Data were collected through interviews and analyzed using Colaizzi’s seven-step thematic analysis. Results: The results of the study described 7 themes related to the perceptions and experiences of drug-resistant tuberculosis HIV/AIDS sufferers who experience loss to follow-up based on life values and stigma, including 1) understanding of HIV/AIDS and tuberculosis; 2) causes of TB and HIV/AIDS clients experiencing loss to follow-up; 3) what happens after experiencing loss to follow-up: economic problems and drug availability; 4) adaptation after experiencing loss to follow-up: comfort; 5) use of herbal medicine as therapy; 6) barriers and support when it comes to control and treatment; 7) hope to recover and regularly taking medication and environmental dilemmas. Conclusion: HIV/AIDS and tuberculosis sufferers who experienced loss to follow-up provide an understanding of experience, including the process of disease transmission and spread as well as antiretroviral drug treatment, anti-tuberculosis drugs, and the side effects they experience. A further problem is the community’s assessment of the condition of the disease. The support and facilities provided affected the issue of needs, both material and psychological.